Numerical closed-form solutions of skin flap surgeries using 3D face models / Nur Nadirah Khairu Najhan - Nur Nadirah , Khairu Najhan (2021)
A computational-based surgical simulation that typically relies on the Finite Element method has added value to surgical planning. A plethora of FE modeling in local flap surgery has been developed to better understand the biomechanics of local flaps. However, to the best of our knowledge, none considered using a three-dimensional head template as a base model as well as associating ethnic and gender demographics. Therefore, the present work aims to address these gaps, including exploring the stress profiles of three common flap designs on their respective anatomic locations. It is expected that incorporating three-dimensional patient-like models into the simulations would provide better post-operative visualization of facial reconstruction instead of two-dimensional planar approaches as well as serves as training aids and pre-operative patient information. The intended study began with creating a set of facial deformities using a Caucasian-like head template. The deformities were formed by cut-extruding a set of local flap designs: advancement, rotation, and rhomboid flaps at three different facial locations: forehead, cheek, and temple, respectively. These local flaps were embedded in the outermost face layer (epidermis). Concurrently, a single layer of skin thicknesses and third-order Yeoh hyper-elastic skin properties were adopted from the work of existing literature and implemented into the face models to accommodate the realization of human skin behaviors. The post-operative simulations demonstrated standard local flap closures along with the commonplaces of peak tensions in which were found consistent with the available literature. Additionally, Burow’s triangles were superimposed on the advancement and rotation flaps to assist the mobility of the flaps towards the defect. The study was then further in applying the original method to Asian-like head templates with a focus on gender-related differences. Rotation and rhomboid flaps demonstrated maximal tension at the apex of the flap for both genders as well as advancement flap in the female face model. However, advancement flap closure in the male face model presented otherwise. Yet, the deformation patterns and the maximal tension of the discussed flaps were consistent with the conventional. Moreover, male face models generated higher stress compared to the female face models with a 70.34% mean difference. Overall, these operations were executed manually and the designed surgery models met the objectives successfully while acknowledging the study limitations. Future work will involve the adoption of multiple layering, pre-stress effects, and specific material properties according to a particular demographic.